THE HEADMASTERâS STRATEGIES IN IMPLEMENTING MANAGEMENT BASED ON SCHOOLS IN SMP MUHAMMADIYAH 4 GEMPOL, PASURUAN - Hadi, Saiful (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2018)
AbstractThis study aims to find out and explore how does the headmaster implementit? what is the obstacle facing him? what strategy is done? This research usesfour approaches that are pedagogies, sociological, juridical and psychological.The sources of the data are primary and secondary. The instruments areinterviews, observation guides, check list observation, and documentation.The research techniques are data reduction techniques, data presentation, andconclusions. From the results of the research of school-based management inSMP Muhammadiyah 4 Gempol, it can be concluded: The headmaster hasimplemented school-based management but the implementation has not fullyimplement school-based management. The headmaster as a leader using SchoolBased Management still needs improvement and improvement of teacherquality and good cooperation with school partners. Constraints faced a) Lackof educational facilities and infrastructure b) lack of teacher competency c)lack of parental support of learning process, d) lack of intensive and maximalsocialization, e) lack of master of technology. Strategies undertaken inimplementing school-based management ie a) doing relationship with relevantagencies to provide the facilities and the infrastructure b) improving teachercompetence by involving teachers in trainings c) doing relationship withparents to improve the quality of education. The implications of this researchis expected for the headmasters and teachers to always perform their dutiesand functions respectively each other. To the teachers of SMP Muhammadiyah4 Gempol, to always strive to improve the professionalism of work for thequality of school education in particular and in general can be better. To therelevant agencies would pay attention to the development of each school.Â Keywords: Strategy, Leadership, Management